Comparison Of Endothelial Cell Count Before And After Phacoemulsification In Grade 2 Nuclear Sclerosis Cataract Versus Grade 4 Nuclear Sclerosis Cataract In Tertiary Care Hospital In Pakistan - Rafi , Piya Muhammad Musammat; Manzoor, Shehzad; Mukhtar, Sarfraz Ahmad; Hussain, Majid; Ilyas, Abdul Rehman; Mehmood, Kashif (Journal of Rawalpindi Medical College, 2025)
Objective: During Phacoemulsification, hardness of the lens opacity has definitive impact on corneal endothelial cells. In our study we provided comparative data for endothelial cell count by comparing Phacoemulsification procedure in grade 2 versus grade 4 cataract. Methods: Our study included 90 patients after taking approval from the Ethical Review Committee from 1st May 2024 to 31st October 2024. Technique of Non-Probability Purposive sampling was used. Patients were selected for the data collection process in the Eye Outpatient Department at the Institute of Ophthalmology, Allied Hospital, Faisalabad. Slit lamp examination was performed on all patients to diagnose cataract. Specular microscopy was done to examine the endothelial cell count before and after phacoemulsification in grade 2 versus grade 4 nuclear sclerosis cataract. Patients were divided into two groups based on the grade of nuclear sclerosis cataract: Group A (patients with grade 2 nuclear sclerosis cataract) and Group B (patients with grade 4 nuclear sclerosis cataract). Results: The mean age of patients was 61.311±3.97 years in Group A and 62.400±3.58 years in Group B. The mean ± SD of baseline endothelial cell count in Group A was 2248.022 ± 132.05 mm2, while in Group B it was 1977.488 ± 180.90 mm2 (p-value <0.05). The mean ± SD of postoperative endothelial cell count after 6 weeks in Group A was 1935.622 ± 165.57 mm2 (mean cell loss), and Group B was 1535.955 ± 177.37 mm2 (mean cell loss; p-value <0.05). Endothelial cell loss% increased from 13.89% in grade 2 nuclear sclerosis cataract to 22.32% in grade 4 nuclear sclerosis cataract. Conclusion: Endothelial cell loss was higher with high grade of nuclear sclerosis cataract ranging from 13.89% in grade 2 to 22.32% in grade 4 cataract.